Pro-angiogenic Activity Discriminates Human Adipose-Derived Stromal Cells From Retinal Pericytes: Considerations for Cell-Based Therapy of Diabetic Retinopathy - Kremer, Heiner; Gebauer, Julian; Elvers-Hornung, Susanne; Uhlig, Stefanie; Hammes, Hans-Peter; Beltramo, Elena; Steeb, Lothar; Harmsen, Martin C.; Sticht, Carsten; Klueter, Harald; Bieback, Karen; Fiori, Agnese (Frontiers in Cell and Developmental Biology, 2020)
Diabetic retinopathy (DR) is a frequent diabetes-associated complication. Pericyte dropout can cause increased vascular permeability and contribute to vascular occlusion. Adipose-derived stromal cells (ASC) have been suggested to replace pericytes and restore microvascular support as potential therapy of DR. In models of DR, ASC not only generated a cytoprotective and reparative environment by secretion of trophic factors, but also engrafted and integrated into the retina in a pericyte-like fashion. The aim of this study was to compare the pro-angiogenic features of human ASC and human retinal pericytes (HRMVPC) in vitro. Proliferation and expression of ASC and HRMVPC markers were compared. Adhesion to high glucose-conditioned endothelial extracellular matrix, mimicking the diabetic microenvironment, was measured. Angiogenesis-promoting features of both cell types and their conditioned media on human retinal endothelial cells were assessed. To identify a molecular basis for the observed differences, gene expression profiling was performed using whole genome microarrays and data were validated using PCR arrays and flow cytometry. Based on multiplex cytokine results, functional studies on selected growth factors were performed to assess their role in the angiogenic support. Despite a distinct heterogeneity in ASC and HRMVPC cultures with an overlap of expressed markers, ASC differed functionally from HRMVPC. Most importantly, the pro-angiogenic activity was solely featured by ASC, whereas HRMVPC actively suppressed vascular network formation. HRMVPC, in contrast to ASC, showed impaired adhesion and proliferation on high glucose-conditioned endothelial extracellular matrix. These data were supported by gene expression profiles with differentially expressed genes. Vessel stabilizing factors were higher expressed in HRMVPC and angiogenesis-promoting factors higher in ASC. Vascular endothelial growth factor receptor-2 inhibition efficiently abolished ASC angiogenic supportive capacities, whereas the addition of angiopoietin-1 and angiopoietin-2 did not alter these effects. Our results clearly show that ASC are pro-angiogenic whereas HRMVPC are marked by anti-angiogenic/EC stabilizing features. These data support ASC as pericyte replacement in DR, but also suggest a careful risk to benefit analysis to take full advantage of the ASC therapeutic features.